Prevalence and associated factors of social phobia among high school adolescents in Northwest Ethiopia, 2021 - Nakie, Girum; Melkam, Mamaru; Desalegn, Getachew Tesfaw; Zeleke, Tadele Amare (Frontiers in Psychiatry, 2022)
Background Social phobia is the third most common mental illness in the world. It harms educational achievement by increasing school absentees and prevents students to participate in class, and this leads to a significant impairment of the emotional, psychological, social, and physical wellbeing of students. The research done regarding social phobia and associated factors among high school students in low- and middle-income countries is limited. Therefore, this study aims to assess the prevalence and associated factors of social phobia among adolescents and have a pivotal role in further investigation. Objectives To assess the prevalence and associated factors of social phobia among high school adolescents in Northwest Ethiopia, 2021. Materials and methods An institutional-based cross-sectional study was conducted from 15 April to 14 May 2021, by using a simple random sampling technique to select a sample of 936 participants after proportional allocation to the six high schools. Social phobia was assessed by using the social phobia inventory (SPIN), independent variables like social support were assessed by Oslo social support scale, substance-related factors by ASSIST, and the rest of the other factors were assessed by structured questionnaires. Binary and multivariate analyses were done to identify factors associated with social phobia. Statistical significance was declared at a 95% confidence interval (CI) of p-value less than or equal to 0.05. Result The prevalence of social phobia among adolescents was found to be 40.2% (95% CI 37.0 to 43.4%). In the multivariable analysis, female sex (AOR = 1.374, 95% CI = 1.016, 1.858), poor social support (AOR = 2.408, 95% CI = 1.660, 3.493), having known chronic medical illness (AOR = 2.131, 95% CI = 1.173, 3.870), having a history of mental illness in the family (AOR = 1.723, 95% CI = 1.071, 2.773), and is highly risky alcohol user (AOR = 1.992 95% CI 1.034, 3.838) were factors significantly associated with social phobia symptoms. Conclusion The overall prevalence of SP among adolescents was high. Therefore, early detection and adequate intervention are crucial to reducing the overall burden of social phobia among adolescents.